1998
DOI: 10.1055/s-2007-995283
|View full text |Cite
|
Sign up to set email alerts
|

Positiv-und Negativsymptomatik bei chronisch schizophrenen Patienten unter Erhaltungstherapie mit Flupentixol-Decanoat im 12-Monats-Verlauf

Abstract: 62 chronic schizophrenics, who after a psychotic exacerbation were stabilized again, were randomized on 3 different maintenance dosages of flupentixol-decanoate and observed for 12 months. 15 (24.2%) patients had a relapse independently of the dose. 34 of the 47 patients without relapse had complete documentations of the follow-up. After 3 to 6 months there was an obvious and constant clinical improvement as assessed by various test inventories. The BPRS-scores for psychopathology, negative and positive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Evidence suggests that flupenthixol is very effective in treating negative symptoms of schizophrenic patients [51]. According to Gruber and Cole [52], flupenthixol is useful as an antidepressant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that flupenthixol is very effective in treating negative symptoms of schizophrenic patients [51]. According to Gruber and Cole [52], flupenthixol is useful as an antidepressant.…”
Section: Introductionmentioning
confidence: 99%
“…When integrating clinical and basic data, the question 'which special neuroleptic treatment should be used for which subgroup of schizophrenic patients' arises. Following the paper of Tandon et al [28] and that of Schooler [36], we used risperidone, a well documented atypical medication in schizophrenia, and flupenthixol, a typical drug (D 2 receptor) with some atypical properties (5-HT 2A ), and documented not only psychopathology but also subjective quality of life and attitude towards medication [22,26,28,30,31,36,51,[53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…As several studies suggest that depot medication with flupentixol might have a positive effect on the long-term course of patients with schizophrenia (Knudsen 1985;Eberhard and Hellbom 1986;Pach et al 1998b), this may bias our results. In our study, the percentage of patients who had received at least one antipsychotic depot medication was substantially higher for flupentixol (10.1% of subgroup) and other first-generation antipsychotics (8.2% of subgroup) than for the second-generation antipsychotics (1.5% of subgroup).…”
Section: Number Of Days Hospitalisedmentioning
confidence: 89%
“…In the flupentixol group, the 'ability to cope with stress', 'feel more relaxed' and the 'ability to achieve something' improved significantly more than in the risperidone group. Evidence also suggested that flupentixol is effective in treating negative symptoms (Pach et al 1998a;Philipp et al 2003;Gattaz et al 2004) and useful as an antidepressant (Gruber and Cole 1991;Budde 1992). These effects are probably based on the different receptor profile of flupentixol compared to other firstgeneration antipsychotics such as haloperidol.…”
Section: Discussionmentioning
confidence: 99%
“…In einer über 12 Monate durchgeführten Untersuchung an chronisch schizophrenen Patienten, deren Zustand sich nach einer akuten psychotischen Exazerbation wieder stabilisiert hatte, ergab sich unter 5 ± 40 mg/2 Wochen für die Scores für Negativsymptomatik der ¹Brief Psychiatric Rating Scaleª (BPRS) und der ¹Scale for Assessment of Negative Symptomsª (SANS) jeweils ein signifikanter Rückgang um bis zu 22 % des Ausgangswertes [14]. In diesem Zusammenhang wird für Flupentixol aufgrund seiner hohen Affinität zu 5-HT 2A -(und 5-HT 2C -) Rezeptoren und Dopamin-D 1 -Re- [39].…”
Section: Depotneuroleptikaunclassified